An Analysis Of Extrinsic Elements In The Collection Of Short Stories Berjuta Rasanya by Tere Liye - Rima Sarah (English Department, Faculty of Humanities, Andalas University, 2022)
The collection of short stories Berjuta Rasanya is one of the literary masterpieces of an Indonesian writer named Tere Liye. This study aims to determine the extrinsic elements that influence the writing of each short story in the book Berjuta Rasanya. This study aims to describe the various extrinsic elements contained in the collection of short stories Berjuta Rasanya. The type of this research is a qualitative research with a descriptive method. The data source of the research is a collection of short stories Berjuta Rasanya by Tere Liye. The data collection techniques in this study were: (1) reading and understanding the collection of short stories Berjuta Rasanya by Tere Liye, (2) coding by underlining sentences containing extrinsic elements in the short story collection Berjuta Rasanya by Tere Liye. The steps of analyzing the data are: (1) reading the recorded data, (2) classifying or recording data according to the researcher's objectives based on the collection of short stories Berjuta Rasanya by Tere Liye, (3) interpreting the data with research objectives, namely: analyzing the collection of short stories Berjuta Rasanya by Tere Liye, and (4) making research conclusions. The results of this study indicate that the extrinsic elements that can be found in the collection of short stories Berjuta Rasanya by Tere Liye are the background of the author's life, psychological elements of the author, the author's social environment, social values, religious values, moral values, and cultural values.